Reconceptualising professional role reconfiguration in healthcare: institutional work and influences around professional hierarchy, accountability and risk - Bergin, Nicola (2016)
This thesis explores the phenomenon of workforce modernisation through the reconfiguration of professional roles, which represents a policy priority in healthcare systems in the United Kingdom (UK) and globally. Heavily informed by conflict or power accounts of professionalism, the literature presents attempts to reconfigure professional roles as opportunities for the reallocation of professional knowledge and expertise and therefore power and status. Existing work emphasises the strategic, competitive activity of professionals to establish, extend and defend jurisdiction in the face of such change. Utilising an organisational neoinstitutional approach this thesis provides a novel theoretical interpretation of the opportunities and threats that the renegotiation of roles presents to the professional groups involved, adding complexity to the accounts that dominate the literature. The thesis draws upon work that describes the evolving nature and function of professionalism to demonstrate that in the contemporary organisational environment, focussed on accountability and risk management, attempts to reconfigure professional roles are understood not only in terms of the transfer of professional knowledge and expertise but the concurrent transfer of accountability for the management of risk. This represents a more complex commodity potentially associated with professional risk in the event of untoward incidents. Using the case of changes to the roles of consultant psychiatrists in the UK National Health Service (NHS) that propose the redistribution of clinical activity and responsibility from psychiatrists across the wider mental health workforce, the thesis demonstrates that rather than competing for jurisdiction associated with the management of significant risk, professionals carefully renegotiate their roles in a manner that ensures the protection, not just of their clients, but of the professionals involved. In this case, despite institutional work from professionals and managers to create change in established practice, concern with accountability for the management of risk drove adherence to traditional, readily accepted and organisationally sanctioned interprofessional boundaries, limiting the degree of change enacted. These findings have important practical implications for those involved in the management of change as well as theoretical implications for our understandings of professional role reconfiguration attempts and the nature of contemporary professionalism more broadly.